Corrigendum to “Achievable Multiplicity partitions in the Inverse Eigenvalue Problem of a graph” [Spec. Matrices 2019; 7:276-290.] - Adm Mohammad; Fallat Shaun; Meagher Karen; Nasserasr Shahla; Plosker Sarah; Yang Boting (Special Matrices, 2020)
We correct an error in the original Lemma 3.4 in our paper “Achievable Multiplicity partitions in the IEVP of a graph”’ [Spec. Matrices 2019; 7:276-290.]. We have re-written Section 3 accordingly.